PROGRAM KEMITRAAN MASYARAKAT PADA KELOMPOK GURU SEKOLAH DASAR TUNAS HARAPAN JAYA DALAM PENERAPAN PROTOKOL PENCEGAHAN INFEKSI COVID-19 - N. W. Widhidewi; P. A. Suryanditha; P. I.B. Apsari; P. Sutisna (Buletin Udayana Mengabdi, 2022)
Plan to implement face-to-face learning at primary schools in the era of Covid-19 pandemic may potentially increase the risk of Covid-19 infection in the teachers, school staff and students. The aim of this community service program was to increase the knowledge and skill of teachers and school staff about health protocols to prevent Covid-19 infection during face-to face learning activities at schools. This program was held at Tunas Harapan Jaya Primary School, with 17 participants comprising teachers and school staffs. The community service was begun with pre-test, followed by a workshop on health protocols to prevent Covid-19 infection, training on 6 steps of hand washing technique, post-test and giving some contributions in the form of automatic thermometer and hand sanitizer and scale apparatus for screening of student`s nutritional status. We also accompanied the teachers and staff to formulate a written procedure about health protocols in school for 1 month. The result of our program showed that there was an 15,3% increase in the participant`s knowledge based on pre-test and post-test scores. All of the participants could demonstrate the correct hand washing technique excellently. We hope that all of the participants could educate another school staff as well as the students to always remember and practice health protocols to prevent transmission of Covid-19 infection in the school. Keywords: Covid-19, teacher, community service, health protocol, school